Evaluation of Growth and Wood Traits in Seven-Year-Old Eucalyptus and Corymbia Species in Southern India - Shukla, S. R.; Kamalakannan, R.; Suraj, P. G.; Vargese, M.; Jayasree, C. E. (Indian Forester, 2022)
Growth and wood traits were evaluated in seven-year-old trees of 7 seedlots from Eucalyptus and Corymbia species in a medium rainfall site in Kerala state. There was significant difference in most traits between the species within the genus. Among Eucalyptus species, E. alba had inferior growth and lower pulp yield (44.5%), but significantly higher basic wood density (753 kg/m3) and volumetric shrinkage compared to E. urophylla and E. pellita. Modulus of rupture (MOR) was also higher in E. alba than other eucalypts, but modulus of elasticity (MOE) was on par with E. pellita. Growth, basic wood density (651 kg/m3), MOR and MOE of E. camaldulensis was comparable, but pulp yield (45.4%) was lower than E. urophylla (46.6%) and E. pellita (47.7%). Corymbia genus had slower growth than major eucalypt species, but C. citriodora had significantly better growth and wood properties than C. torelliana. Based on the basic wood density, the tested species can be classified into three categories - low density: E. pellita, C. torelliana, (519-567 kg/m3); medium density: E. camaldulensis and E. urophylla, (642-657 kg/m3), and high density: E. alba and C. citriodora species (724-769 kg/m3). High positive correlation was found between basic wood density and other wood traits volumetric shrinkage and flexural strength (MOR) across the tested species.